Laparoscopic-enhanced recovery after surgery protocol for incarcerated inguinal hernia: a paradigm shift toward precision emergency herniology - Zhu, Xinqiang; Shan, Siwei; Zhang, Jianwei (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the safety and efficacy of a modified Enhanced Recovery After Surgery (ERAS) protocol integrated with laparoscopic repair for incarcerated inguinal hernia, comparing outcomes with conventional open surgery.MethodsThis single-center retrospective cohort study (2019-2024) included 200 patients with incarcerated inguinal hernia. These patients were assigned to the laparoscopy group or the open group (in a 1:1 ratio). Propensity score matching (PSM) balanced the baseline characteristics. ERAS intervention includes preoperative counseling, multimodal analgesia and forced early activities. Continuous variable: Independent t-test or Mann–Whitney U; Categorical variables: Chi-square test or fish test; Multivariate logistic regression was used for hazard ratio analysis.ResultsAfter PSM (80 pairs), the laparoscopic group demonstrated significantly lower overall complications (9% vs. 38%, P = 0.007), including reduced surgical site infections (6% vs. 18%) and postoperative ileus (4% vs. 14%). Laparoscopy shortened hospital stays (3.1 vs. 5.6 days, P < 0.001), accelerated bowel function recovery (16.5 vs. 26.3 h, P < 0.001), and decreased opioid use (12.4 vs. 32.7 mg, P < 0.001). Eighteen cases required open conversion (15 for intestinal resection). No large bowel resections occurred.ConclusionLaparoscopic repair of incarcerated inguinal hernias integrated with ERAS protocols demonstrates significant clinical efficacy, effectively reducing postoperative complications and accelerating recovery, thereby establishing itself as a recommended standard for widespread clinical adoption.